A Dental Response to the COVID-19 Pandemic—Safer Aerosol-Free Emergent (SAFER) Dentistry - Benzian, Habib; Niederman, Richard (Frontiers in Medicine, 2020)
Dental services are significantly impacted by the COVID-19 pandemic. Many dental procedures carry a high infection risk for providers and patients due to spread of aerosols. Public health agencies and professional associations issued guidelines for enhanced infection control, personal protection equipment, limiting care to urgent or emergency services. However, there is no dental service concept for pandemic disaster preparedness or response that might be applied. Moreover, pathways to dental care provision in a post-pandemic future with persisting risks are needed. We propose Safer Aerosol-free, Emergent Dentistry (SAFER Dentistry) as one approach to dental services during and emerging from pandemics. The concept’s starting point is the identification of the most common patient needs. Common treatments addressing the most frequent needs are replaced with alternative interventions involving a lower infection risk because they do not generate aerosols. SAFER Dentistry is innovative, avoiding risk, and responds to the requirements of a pandemic and post-pandemic emergence where the risk of airborne disease transmission remains high. SAFER Dentistry thereby ensures continuity of dental services while protecting providers and patients from infectious pathogens. Moreover, SAFER Dentistry allows dental service providers to remain operational and generate income even under pandemic conditions. Potential implementation and policy options for SAFER Dentistry include universal availability without co-payments by patients and a uniform bundled payment scheme for providers to simplify budgeting, reimbursement and to simplify administration during a pandemic. Adaptations and adjustments of the concept are possible and encouraged, as long as the principle of avoiding aerosol-generating procedures is maintained.